Vapor-etching honeycomb-like zinc plating layer for constructing anti-corrosion lubricant-infused surfaces - Song, Xiaorui; Li, Na; Wang, Zhongshan; Li, Shuangjian; Hou, Yuanyuan (Frontiers in Chemistry, 2023)
Biomimetic lubricant-infused porous surfaces are developed and applied in omniphobicity and corrosion protection, which exhibited great advantages compared to superhydrophobic surfaces. Herein, superhydrophobic Fe@E-Zn@PFOA was prepared via the electrodeposition of laminated Zinc coating, further vapor etching and postmodification with perfluoro caprylic acid. The facile, inexpensive and environmentfriendly water vapor etching process can form porous honeycomb-like structure.Moreover, the perfluoropolyether lubricant was wicked into the porous and superhydrophobic surfaces, obtaining lubricant-infused surface of Fe@E-